(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article explores innovative methodological approaches to enhance the teaching of upbringing in grades 5-6, focusing on holistic curriculum design, interactive learning, technology integration, social emotional learning, student-led initiatives, parental involvement, cultural sensitivity, and fostering lifelong learning and civic engagement. The methods discussed aim to create a nurturing educational environment where students develop strong moral character, empathy, and a sense of social responsibility.